Palladium-Catalyzed Decarboxylative Formal (4+2) Cycloaddition of Vinyl Benzoxazinanones with 3-Nitroindoles - Bird, Melissa J.; Wales, Steven M.; Richardson, Christopher; Hyland, Christopher J. T. (Synlett, 2020)
A diastereoselective palladium-catalyzed dearomative formal (4+2) cycloaddition between vinyl benzoxazinanones and 3-nitroindoles has been developed. This reaction provides a concise route to tetrahydro-5H-indolo[2,3-b]quinolines in excellent yield (up to 94%) and diastereoselectivity (up to >98:2), with versatile functional handles including vinyl, nitro, and free NH groups.
Keywords: dearomatization; Pd catalysis; indoles; vinyl benzoxazinanones